Solidarność Walcząca . tygodnik organizacji Solidarność Walcząca Oddz. Poznań, no. 145, 1989 - Res; Frankiewicz, Maciej; Fiećko, Jerzy; Filipek, Włodzimierz (Agencja Informacyjna Solidarności Walczącej [various acronyms], 1989)
Creation and circulation: From issue no. 16=232(1990) published legally titled Solidarność Walcząca : kwartalnik polityczny. Issue no. 16 is the consequtive numer of the Poznań edition of Solidarność Walcząca, no. 232 is the consequtive number of Solidarność Walcząca perviously published in Wrocław